2005
DOI: 10.1029/2005gl022621
|View full text |Cite
|
Sign up to set email alerts
|

The El Niño–Southern Oscillation and daily temperature extremes in east Asia and the west Pacific

Abstract: The numbers of warm nights and hot days, across most of the east Asia – west Pacific region, increase substantially in the year after the onset of an El Niño event. The number of cool days and cold nights tend to decrease, although the relationship with El Niño is weaker for these variables. The relationship is confounded, for warm nights and hot days, by a strong increasing trend in the numbers of extremes not matched by a trend in the El Niño. Removal of this trend leads to even stronger correlations with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 4 publications
3
38
0
1
Order By: Relevance
“…The existence of strong correlations with substantial lead time (significant at 5% level for cold events, and 1% level for hot events) indicates potentially useful prediction skills. These results are similar to those reported by Nicholls et al (2005) who showed that the ENSO has strong links with variations in the annual frequency of temperature extremes in East Asia-West Pacific Region and the predictions of frequencies of hot and cold events could be made with some skill from NINO3.4 SSTs as early as May in the preceding year. They have also shown that the annual number of cool days tends to be lower in the year following the onset of El Niño event, whereas the annual number of hot days tends to be higher.…”
Section: Correlation Of Extreme Temperature Indices With Enso Indexsupporting
confidence: 80%
See 2 more Smart Citations
“…The existence of strong correlations with substantial lead time (significant at 5% level for cold events, and 1% level for hot events) indicates potentially useful prediction skills. These results are similar to those reported by Nicholls et al (2005) who showed that the ENSO has strong links with variations in the annual frequency of temperature extremes in East Asia-West Pacific Region and the predictions of frequencies of hot and cold events could be made with some skill from NINO3.4 SSTs as early as May in the preceding year. They have also shown that the annual number of cool days tends to be lower in the year following the onset of El Niño event, whereas the annual number of hot days tends to be higher.…”
Section: Correlation Of Extreme Temperature Indices With Enso Indexsupporting
confidence: 80%
“…As strong trends have been identified by earlier studies in the temperature extremes over Indian region (Kothawale et al, 2006), the correlations between NINO3.4 SSTs and indices are calculated on linearly detrended data as well as on the 'raw' data. Similar approach was used by Nicholls et al (2005) while examining the relationship between ENSO and daily temperature extremes in East Asia and West Pacific. However, it has been found that the detrending approach made very little difference to the correlation results.…”
Section: Data and Methods Of Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Hence continuous wet days are substantially decreasing in recent period. A Similar type of analysis has been done by Nicholls et al (2005) for hot/cool days and warm/cold nights. …”
Section: Trend Analysismentioning
confidence: 98%
“…Many publications provide evidence of correlations between El Niño events and atmospheric circulations in the Northern Hemisphere (e.g. see Lau et al, 2005;Nicholls et al, 2005;Mokhov and Smirnov, 2006;Müller and Roecker, 2006), as the sea surface temperature anomalies in the tropics can cause a remote teleconnection response in the atmospheric circulation. It is therefore not unrealistic to expect that atmospheric teleconnections during warm ENSO events lead to an anomalous anticyclonic atmospheric circulation pattern (higher atmospheric pressure) developing over the Barents Sea, instead of the more usual cyclonic conditions observed during winter months (e.g.…”
Section: N Stepanov Et Al: the Link Between The Barents Sea And mentioning
confidence: 99%